INFLUENCE OF INACTIVATION METHODS ON PATHOGEN DIAGNOSTICS BY MEANS OF INSTRUMENTAL METHODS - Kubicek, Oldrich; Salplachta, Jiri; Horka, Marie; Placakova, Hana; Lunerova, Kamila (MATTER: International Journal of Science and Technology, 2019)
Mass spectrometry as an identification method for microorganisms is rapidly developing in the last years. However, this method is not suitable for detection of agents in complex matrices and it has to be preceded by clean-up procedures and particular agent’s concentration. In the case of high-risk pathogens, such a separation method may pose a hazard for the laboratory staff. Therefore, various methods for pathogen inactivation were studied. Their influence on pre-concentration and separation of microorganisms by means of preparative and capillary isoelectric formation was studied. Most of the disinfectant agents disrupted the cells integrity and made their following separation impossible. The most promising was freeze-dry samples inactivation using hydrogen peroxide vapor at 300 ppm concentration. Inactivation of the lyophilized bacterial agents caused an only inconclusive shift of mass spectra in MALDI-TOF MS analysis, but it caused a quite significant change of isoelectric point. Inactivation of bacterial spores required at least 2 hours of exposure. Increased vapor concentration caused damage to the cells. Heating up the samples up to 60 °C enabled to increase the vapor concentration and made the inactivation faster without influencing the mass spectra. Moreover, the influence of thermal inactivation of bacterial agents at 60 °C for 16 hours was studied. There was no significant change in mass spectral in MALDI-TOF MS analysis, but it did not work for sporulating bacterias. Simultaneously, the longtime of inactivation was a significant drawback. The possibilities of the detection and the identification of inactivated pathogens are an object of ongoing research.